A greener approach for resource recycling: Manganese bioleaching. (July 2016) - Ghosh, S.; Mohanty, S.; Akcil, A.; Sukla, L.B.; Das, A.P.
Abstract: In view of unremitting diminution of mineral resources, rising energy economics along with increasing global consumption of Manganese (Mn), development of environment friendly technologies for tapping alternate sources of Mn has gained importance lately. Mn recovery from mining residues using conventional approaches is extremely expensive due to high capital and energy costs involved. However lean grade ores present in millions of tons awaits the development of competent and cost effective extractive process. Mn recovery by biomining with diverse microbes is thereby recommended as a superior and green alternative to the current pyro metallurgical techniques. The synergistic effects of different factors are known to influence microbial leaching of mineral ores which includes microbiological, mineralogical, physicochemical and process parameters. Bacterial bioleaching is mostly due to enzymatic influence, however fungal bioleaching is non enzymatic. Genomic studies on microbial diversity and an insight of its metabolic pathways provides unique dimension to the mechanism of biomining microorganisms. The extraction of Mn has a massive future prospective and will play a remarkable role in altering the situation of ever-decreasing grades of ore. This review aims to encompass the different aspects of Mn bioleaching, the plethora of organisms involved, the mechanisms driving the process and the recent trends and future prospects of this green technology. Highlights: Microbial diversity involved in manganese bioleaching has been highlighted. Mechanism of manganese bioleaching have been described. Process parameters for efficient Mn recovery has been discussed. Recent development and future trends in manganese mining has been suggested.